1980
DOI: 10.1159/000241251
|View full text |Cite
|
Sign up to set email alerts
|

The Pentose Phosphate Pathway in Brain during Development

Abstract: Sprague-Dawley rats were delivered in our laboratory and decapitated at ages varying between 1 and 60 days. The concentrations of 6-phosphogluconate in extracts of the brain were determined in these litters and in adult rats. The highest content of 6-phosphogluconate was seen in brains of 3-day-old rats when it was at that age more than six times the adult level. Turnover rates for this same compound were determined by an in vitro technique at ages 1, 3 and 12 days and in the adult. We conclude that the pentos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…These findings support the view that the rate of lipid synthesis regulates the HMS during much of develop ment in these ganglia, presumably by converting NADPH to the NADP+ needed for HMS activity, whereas other factors, such as RNA synthesis, may place additional demands on the HMS at other times and in other tissues (Horecker, 1965;Lajtha et al, 1981, p. 339;Hakim et al, 1980;Larrabee, 1987, and additional literature cited therein).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…These findings support the view that the rate of lipid synthesis regulates the HMS during much of develop ment in these ganglia, presumably by converting NADPH to the NADP+ needed for HMS activity, whereas other factors, such as RNA synthesis, may place additional demands on the HMS at other times and in other tissues (Horecker, 1965;Lajtha et al, 1981, p. 339;Hakim et al, 1980;Larrabee, 1987, and additional literature cited therein).…”
Section: Discussionsupporting
confidence: 71%
“…Possibly the latter was due to the high rate of RNA synthesis shown at this time in Fig. 5 (Hakim et al, 1980). However, the mechanism by which RNA metabolism would accelerate the HMS is unknown, and the pentose needed for RNA formation could alternatively be supplied via the nonoxidative pathway of pentose synthesis without change in the HMS (Horecker, 1965).…”
Section: Discussionmentioning
confidence: 90%
“…The present experiments failed to demonstrate a rise and fall of RNA synthesis corresponding to the changes in the HMS. Thus the demand of RNA metabolism for ribose-P cannot be regulating the HMS in these sympathetic ganglia at this stage of development, despite arguments for such a relationship in the brains of rats (Hakim et al, 1980). In this connection it should be noted that ribose-P for RNA synthesis is produced not solely by the oxidative portion of the pentose cycle (the HMS), but also by the nonoxidative portion of this cycle, which starts with fructose-6-P and is independent of NADP' (e.g., Horecker, 1965;Lehninger, 1975).…”
Section: Discussionmentioning
confidence: 95%
“…However, since the HMS forms many products other than NADPH it is alternatively possible that this pathway might be regulated primarily according to the need for one or more of its other products. For example, Hakim et al (1980) have recently suggested a regulation for the production of the ribose-P used in RNA synthesis. Moreover, since NADPH is formed by reactions other than the HMS, the NADPH for lipid synthesis might come from other sources.…”
mentioning
confidence: 99%
“…On the other hand, 6-phosphogluconic acid was reduced in all three LS cell lines. High concentrations of this metabolite have been associated with an active pentose phosphate pathway in early brain development in rats (Hakim et al, 1980) and its supplementation increased the diameter of neurospheres derived from the embryonic Ts1Cje mouse model of Down syndrome (Seth et al, 2020). In addition, hydroxyphenyllactic acid was elevated in DLD and PDH mutant organoids but downregulated in MT-ATP6/PDH.…”
Section: Resultsmentioning
confidence: 99%